Edukasi Pentingnya Meningkatkan Pola Hidup Sehat Pada Lansia - Linawati Togatorop; Dwi Argita Br Tarigan; Junita Putri Malem Br Barus; Agusdin Triade M Gea; Chani Lya E Sianipar; Isabella T. Sembiring (STIKES Columbia Asia Medan, 2024)
Elderly individuals constitute a demographic group vulnerable to various degenerative diseases due to the aging process. Enhancing the importance of adopting healthy lifestyles among the elderly has become a primary focus in efforts to improve their quality of life. Education on healthy living plays a crucial role in aiding the elderly in understanding and implementing healthy behaviors. Through directed educational approaches, seniors can acquire knowledge regarding the significance of aspects such as balanced nutrition, regular physical activity, stress management, as well as adherence to medication and routine health check-ups. With an increased awareness of the importance of healthy lifestyles, the elderly can reduce the risk of various chronic diseases such as diabetes, heart disease, osteoporosis, and cancer. Furthermore, adopting healthy lifestyles can also enhance independence and overall quality of life in the elderly. Therefore, sustained educational efforts by healthcare professionals and families are essential to provide a profound understanding of the importance of healthy living among the elderly, enabling them to lead their later years with optimal quality of life.